Institutional arrangements for the use of treated effluent in irrigation, western Cape, South Africa - Saldias, C.; Speelman, S.; van Koppen, Barbara; Huylenbroeck, G. van (Informa UK Limited, 2016)
Wastewater is increasingly regarded as a valuable resource, but to fully and safely exploit the potential, sound institutional arrangements governing its reuse are crucial. This article presents a case study of a self-managed irrigation scheme in Western Cape, South Africa, that uses treated effluent directly, formally and safely. By applying the Institutional Analysis and Development framework, the variables within the context, action arena and patterns of interaction that have enabled this outcome are systematically identified and evaluated. Key variables include: water scarcity; an effective policy and regulatory framework; public pollution prevention awareness; self-organization; and capital-intensive water use linked to profitable markets.